Belajar SenangJer: A Mobile Application for Illiterate Indigenous Adults - Xian, Ong Shu; Mat Aji, Zahurin; Zakaria, Nur Haryani; Mohd Khalid, Al Hanisham; Awang, Hapini (Multidisciplinary Applied Research and Innovation, 2023)
During the Fourth Industrial Revolution (IR 4.0) era, personal electronic devices such as smartphones, laptops, and computers have become common in an individual’s daily activities. These devices have been used to communicate with others through various social media platforms such as Facebook, Youtube, Wechat, Whatsapp, and others. When the globe is facing the pandemic Covid-19, the importance of the devices had become more significant, along with the increased usage of digital wallets to enable contactless payments. Without literacy skills, an individual is far more likely to live in poverty and may be isolated in a world increasingly dependent on electronic devices. Although the Government of Malaysia has been putting a lot of effort to ensure that indigenous people’s education system is at a reasonable level, there are no significant and robust changes. The illiterate indigenous adults might still be left behind due to their inability to read. Thus, the main objective of this study is to develop a specialized user-friendly mobile educational application prototype to reduce the illiteracy rate among indigenous adults in Malaysia Personal Extreme Programming (PXP), which is the derivative of the Extreme Programming (XP) of the agile method was adopted to develop the mobile. The application is being developed with the intention to reduce the illiteracy rate among indigenous adults in Malaysia. The overall findings indicate that respondents are satisfied with Belajar SenangJer as it facilitates the learning of Malay language through flashcards and videos. In the future, the user interface of Belajar SenangJer could be improved by providing a voice guidance function and matching games. The application could be expanded to learn more languages, such as English and Mandarin.